Genetic Variability Analysis of Medicinally Important Acacia nilotica (L.) Willd. ex Delile Tree based on RAPD “Random Amplified Polymorphic DNA” Markers - Wadah Osman; Haytham Hashim Gibreel; Mona Mohamed salih; Mohamed A El- Sakhawy; Reham M. Samra; Ahmed Ashour (Natural Resources for Human Health, 2026)
Arbitrarily amplified dominant DNA markers (random amplified polymorphic DNA (RAPD), SCoT, and branch point signal (BPS)) were used to evaluate the genetic relationship between three subspecies of Acacia nilotica in the Sudan (nilotica, tomentosa, and adstringens) and a new group that was observed within Sudan’s A.nilotica populations with intermediate morphological traits between the subspecies tomentosa and nilotica. DNA was extracted from seeds that were collected from 28 A. nilotica populations representing the subspecies nilotica (10 populations), subspecies tomentosa (11 populations), the subspecies adstringens (3 populations), and the new group (4 populations) through the agro-ecological zones of the Sudan. A total of 48 primers (8 SCoT, 12 BPS, and 28 RAPD) were tested, of which 16 primers (33.33%) showed polymorphism (2 SCoT, 3 BPS, 11 RAPD) within the studied populations and used for further genetic evaluation. The selected primers amplified 142 bands in the range of 1.39–0.38 kbp, of which 102 were polymorphic (71.27%) among the studied populations with an average of 8.88 bands per primer as well as an average of 59.90% and 0.2175 of the allele frequency and gene diversity (expected heterozygosity), respectively. Spearman’s similarity coefficient indicated high genetic similarity (92.07%) between the new group and the subspecies nilotica, followed by 90.09% and 46.29% with subspecies tomentosa and adstringens, respectively. The genetic dendrogram based on UPGMA clustering analysis grouped the new group with the subspecies nilotica and tomentosa in one cluster, indicating hybridization between them, while the subspecies adstringens was alone in the second cluster.